(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article offers a philosophical analysis of artificial intelligence within a neo-Marxist framework of labor theory, alienation, and the concept of species-being. It examines the transformation of labor under conditions of digital capitalism and algorithmic rationality. Artificial intelligence is interpreted as a dual phenomenon: on the one hand, as a means of expanding human universality and cognitive capacities; on the other, as a mechanism of digital alienation, algorithmic control, and concentration of power. Special attention is given to the phenomena of pseudo-creativity, post-labor, and digital exploitation. The study concludes that the future of labor and human freedom depends not on the technical nature of AI itself, but on the socio-political forms of its institutional implementation and regulation.